DEVELOPMENT GUIDED INQUIRY-BASED FLIPPED CLASSROOM LEARNING SYSTEM FOR INDUSTRIAL REVOLUTION 4.0 ERA ON CHEMICAL BONDING MATERIAL USING LMS MOODLE - Dian Pratiwi; Mawardi Mawardi (Pancaran Pendidikan, 2022)
Characterization of education in the 4.0 industrial revolution era uses digital technology in learning. Therefore, this study aims to develop a guided inquiry-based flipped classroom learning system using LMS Moodle on chemistry class X SMA/MA and to determine the level of validity and practicality of the product developed. The results of processing the validity test data are 0.88, which indicates a valid category. While the results of processing the practicality test data with an average of 89% for students categorized as very practical and an average of 94% practicality for teachers with very practical categories. Overall, the study results indicate that the guided inquiry-based flipped classroom learning system using LMS moodle on chemical bonding material for class X SMA/MA is valid and practical.